Folic acid functionalization for targeting self-assembled paclitaxel-based nanoparticles. Issue 54 (12th December 2022) - Colombo, Eleonora; Coppini, Davide Andrea; Maculan, Simone; Seneci, Pierfausto; Santini, Benedetta; Testa, Filippo; Salvioni, Lucia; Vanacore, Giovanni Maria; Colombo, Miriam; Passarella, Daniele
Abstract : Self-assembled hetero-nanoparticles are obtained by mixing paclitaxel and folic acid conjugates. Abstract : Hetero-nanoparticles self-assembled from a conjugate bearing folic acid as the targeting agent, and another bearing paclitaxel as the active agent are reported. Hetero-nanoparticles containing varying percentages of folic acid conjugates are characterised, and their biological activity is determined.